If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5a-6a=3-5a
We move all terms to the left:
5a-6a-(3-5a)=0
We add all the numbers together, and all the variables
5a-6a-(-5a+3)=0
We add all the numbers together, and all the variables
-1a-(-5a+3)=0
We get rid of parentheses
-1a+5a-3=0
We add all the numbers together, and all the variables
4a-3=0
We move all terms containing a to the left, all other terms to the right
4a=3
a=3/4
a=3/4
| 53/3n=8 | | -10-5k=4k | | 5x+9=-4+18 | | 10/x=3/12 | | z+4/3=4 | | -16-7(7a+3)=23-2a | | 6x+7=13+4x | | c=8+3c | | 14=2u+6 | | -3=5x-4x2 | | -5g-2g=12 | | 21r*2(2)+47r-24=0 | | g+12/4=4 | | 1/2-5/8x=7/8+1/2 | | -8q=-9-7q | | 9=2w-17 | | 500-25x=500 | | 6+8x=5+10x | | -3n(5n+3)=0 | | 8y-3y=5 | | j/4+11=-10 | | 9(k-4)-7k=2(k+8) | | 23x=100(13) | | -17r=-16r-4 | | 12.26x+0.08=13.01x+0.15 | | 4.12-1.14x=4x-1.791 | | 3(n-5)=34 | | 2(2x+3)=-5(2x-3)-3x | | 1k+33=3k | | 2=s2 | | x^2=232x | | 31=-8w+5(w+5) |